MILITARY EDUCATION IN ENSURING COMBAT TRAINING OF THE ARMED FORCES - Ismatov Mamasobir Maxamadievich (Scholar Express Journal, 2022)
All fields underwent drastic reform once the Republic of Uzbekistan attained independence, and the aspiration of producing the ideal generation was designated our primary objective. Each nation's implementation of defense carries out the maintenance of both internal and external security while enhancing the operations of social institutions and military mechanisms. This is one of the key strategic tasks for each nation. The e stablishment, training, and use of military power for the accomplishment of objectives by diverse social organizations constitutes the state's complex of activities known as military activity. This article offers feedback and feedback on military education in order to guarantee the Armed Forces' battle readiness.
Keywords: Military Education; Defense; Officers; Armed Forces